High levels of unprotected anal intercourse and never testing for HIV among men who have sex with men in Nigeria: evidence from a cross-sectional survey for the need for innovative approaches to HIV prevention. Issue 8 (12th July 2013) - Vu, Lung; Andrinopoulos, Katherine; Tun, Waimar; Adebajo, Sylvia
Abstract : Objectives: To describe sexual risk behaviour, correlates of unprotected anal intercourse (UAI) and never testing for HIV and its implications for HIV prevention interventions among men who have sex with men (MSM) in Nigeria and other similar contexts. Methods: A cross-sectional survey was administered to 712 MSM in Abuja, Ibadan and Lagos, recruited through respondent-driven sampling (RDS). Levels of sexual risk behaviour and never having tested for HIV prior to the survey were calculated using weighted data for each city and unweighted data for the pooled sample. Correlates of UAI and never testing for HIV were determined using multiple logistic regression. Results: The risk for HIV and STI among MSM in Nigeria is high, with 43.4% reporting UAI at last sex, 45.1% never having been tested for HIV and 53.9% reporting exchange of sex for resources in the past 6 months. Correlates of UAI in multivariate analysis included living in Ibadan, marriage or cohabitation with a woman, identification as bisexual, not having tested for HIV and being HIV-positive. Correlates of not having tested for HIV in multivariate analysis included living in Ibadan, young age, less education, unemployment and report of UAI. Conclusions: HIV testing is low and associated with UAI. Findings merit targeted and innovative approaches for HIV prevention for MSM, especially access to HIV self-testing. Attention to social and structural determinants of health-seeking and sexual risk behaviour is also needed, including the criminalisation of homosexuality and social marginalisation of MSM.